The “State Interest” and Humanitarian Diplomacy of Oliver Cromwell - L. I. Ivonina (Vestnik MGIMO-Universiteta)
The 16th–first half of the 17th century was a vital period for the emergence of international law, sovereignty, and the modern international system. European sovereigns also started considering at that time what today would be termed humanitarian issues in foreign policy. They relied in this mostly on the contemporary theological thought and the nascent “Law of Nations,” which fostered a discourse opposing the extremes of government (tyranny). The article analyzes one of the most vivid examples of such humanitarian foreign policy – foreign intervention by the Lord Protector of the English Republic, Oliver Cromwell, in the Duchy of Savoy in 1655 to protect the Waldensian Protestants, who suffered persecution there. Contrary to the modern historiography, the article argues that Cromwell did not abandon all other state considerations in questioning the conclusion of the Anglo-French alliance against Spain to stop the repression against the Waldensians. Cromwell’s humanitarian policy was carried out in line with Realpolitik. Aware of the complicated domestic political situation in France and of the goals of French foreign policy, he was sure that Prime Minister Cardinal Mazarin was unlikely to give up the alliance with London in response to the London’s support of the Protestant subjects of the Duke of Savoy. Cromwellian Foreign Policy in SavoyPiedmont demonstrates one of the most significant cases of implementing the humanitarian principles in international relations. At the same time, Oliver Cromwell did not infringe upon the interests of his own country. On the contrary, despite the financial costs of maintaining special embassies and a fleet in the Mediterranean and creating the Waldensian Relief Fund, the support of the persecuted in Piedmont demonstrated the strength and authority of the English state.